Rapid evidence profile #70: Strategies for enhancing public-health-focused data literacy - Bhuiya, AR; Jaspal, A; Grewal, E; Dass, R; Wilson, MG (My University, 2024)
An overview of the best available research evidence from around the world (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about strategies for enhancing public-health-focused data literacy in response to a decision-maker’s request.
Keywords: strategies; public health; data; literacy